Removal of Phenol from Aqueous Solution by Activated Clay - Bouabdesselam, H. (Asian Journal of Chemistry, 2016)
Activated clay has been employed to remove phenolic compounds, a common contaminant in wastewaters, being generated from petroleum and petrochemicals, coal conversion and phenol-producing industries. Because of its high surface area per unit area, activated carbon is the most effective adsorbent and exhibits high capacity for adsorption of phenolic compounds. Kinetics and isotherm studies were conducted to evaluate the adsorption capacity of natural and activated clay. The effect of contact time, pH, initial adsorbate concentration and temperature were studied. In comparison between the capacity adsorption of natural and activated clay, it has been seen that the activated clay adsorbs more than natural clay.